2010
DOI: 10.1055/s-0029-1246219
|View full text |Cite
|
Sign up to set email alerts
|

Large Cystic Hypoglossal Schwannoma with Fluid-Fluid Level: A Case Report

Abstract: Hypoglossal schwannomas are rare skull base tumors. Furthermore, cystic hypoglossal schwannomas are extremely uncommon. We report the first case of a large cystic hypoglossal schwannoma with a fluid-fluid level. A 36-year-old woman presented with increased intracranial pressure and cerebellar signs without hypoglossal nerve palsy. Magnetic resonance imaging showed a predominantly cystic mass with a fluid-fluid level in the foramen magnum region extending into the hypoglossal canal. The intracranial tumor was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In almost all cases, there are varying degrees of paresis of the HyN, which appear as ipsilateral deviation, hemiatrophy and fasciculations of the tongue. These symptoms may be accompanied by hoarseness, intermittent-to-persistent headaches, dysarthria, slurred speech, swallowing difficulties and throat cramps (2,4,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Whereas the effects on the specific functions of the nerve may be attributable to the local damage of the tumour on the nerve, these types of lesions, particularly when they increase in volume, may determine mass effects on surrounding or adjacent structures; for example, Mariniello et al (19) reported on the case of a patient who exhibited signs of cerebellar ataxia, right-sided hypotonia and increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In almost all cases, there are varying degrees of paresis of the HyN, which appear as ipsilateral deviation, hemiatrophy and fasciculations of the tongue. These symptoms may be accompanied by hoarseness, intermittent-to-persistent headaches, dysarthria, slurred speech, swallowing difficulties and throat cramps (2,4,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Whereas the effects on the specific functions of the nerve may be attributable to the local damage of the tumour on the nerve, these types of lesions, particularly when they increase in volume, may determine mass effects on surrounding or adjacent structures; for example, Mariniello et al (19) reported on the case of a patient who exhibited signs of cerebellar ataxia, right-sided hypotonia and increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The second proposed mechanism is hemorrhage, typically of unclotted blood. The red blood cells or the products of red blood cell breakdown constitute the inferior fluid layer, while serous blood constitutes the superior fluid layer based upon sedimentation (2, 4,6,8,14). The present authors consider the second mechanism to be more accurate, since unclotted blood was observed in all the cases reported in the current study.…”
Section: A B C D E Discussionmentioning
confidence: 50%
“…Therefore, surgery is the optimal treatment strategy for such patients. Although cystic VSs with fluid-fluid levels indicate greater adhesiveness, it is essential that total resection is performed during the initial surgical procedure due to the tendency for accelerated regrowth of residual cystic schwannoma (8,18).…”
Section: A B C D E Discussionmentioning
confidence: 99%
See 2 more Smart Citations